Pendapatan Nasional Dalam Perspektif Ekonomi Islam - Asyari Hasan; Alim Saparuddin Harahap; Maulida Tsaqifa Az-Zahra; Muhamad Ibrahim; Annisa Amalia Zahra (Eco-Iqtishodi : Jurnal Ilmiah Ekonomi dan Keuangan Syariah, 2023)
The understanding of national income in both conventional and Islamic economics is examined in detail in this study. This study aims to comprehend the definition of national income, Islamic economics' perspective on the national approach, and the factors that influence the national approach. The strategy utilized in this examination is a library of research techniques and decisive reasoning from the creator. The literature review and a number of pertinent works related to the main topic of discussion serve as the basis for the discussion in this study. According to the findings of this study, a nation's national income is the total amount a community in a country receives in a single year. Public pay can likewise be estimated utilizing pointers like GDP (Gross domestic product) or Gross Public Pay (GNI), which measure the worth of all labor and products created within the limits of a nation or by residents of a country. From the point of view of Islamic economics, ghanimah, zakat, alms, infaq, ushr, jizyah, kharaj, mining taxes and waqf are all sources of national income. Factors that impact pay incorporate total interest and supply, utilization and reserve funds, and venture.